Outcome of curcumin-based photodynamic therapy in endodontic microsurgery: A case report - Lucas Peixoto de Araújo; Analu Rodriguez Marchesin; Lucas Pinto Carpena; Leandro Bueno Gobbo; Nadia de Souza Ferreira; José Flávio Affonso de Almeida; Caio Cezar Randi Ferraz (Photodiagnosis and Photodynamic Therapy)
Introduction: Persistent apical periodontitis after root canal treatment may require surgical retreatment when non-surgical options are ineffective or impractical due to anatomical challenges or iatrogenic errors. Endodontic microsurgery (EMS) is a precise technique that aims to overcome extraradicular biofilm and root morphology issues. Photodynamic therapy (PDT) is an emerging supplementary disinfection approach that utilizes a photosensitizer agent and light to eliminate microorganisms through oxidative reactions. Report: A 60-year-old male with persistent apical periodontitis in a left maxillary first molar underwent non-surgical root canal retreatment followed by surgical reintervention due to anatomical complexities. During surgery, PDT was performed using a novel curcumin-based photosensitizer agent. After the procedure, the tooth was retrofilled with bioceramic cement, and photobiomodulation was applied to enhance tissue healing. One year post-surgery, the patient exhibited complete periradicular repair and remained asymptomatic. Discussion: EMS is considered a last resort to salvage an endodontically treated tooth and has shown moderate success rates. PDT has demonstrated promise in improving periapical healing and reducing microorganisms. In this case, curcumin, diluted with 2 % chlorhexidine gel, served as an effective photosensitizer agent with antimicrobial properties. Moreover, performing photobiomodulation aided in cell recovery and reduced postoperative discomfort. Conclusion: The proposed EMS treatment protocol with PDT using curcumin yielded positive outcomes in this case report. Further randomized clinical trials are necessary to assess the efficacy of this approach in EMS. Additionally, further research on curcumin-based photosensitizer agents encapsulated in nanoparticles and enhanced antimicrobial agents is recommended to refine this treatment protocol for routine use.